Strategi Kebijakan Luar Negeri Timor Leste Untuk Masuk Keanggotaan ASEAN (2019–2025) - Aisyah Adinda Rachma; Alya Rafeyfa Hadi; Chania Deseria Rahmadani (Jurnal Transformasi Global, 2025)
This article examines Timor Leste’s foreign policy strategy for becoming a full member of ASEAN between 2019 and 2025. Timor Leste, a recently independent small power with limited institutional, political, and economic capacity, adopted adaptable and accommodating strategies to meet ASEAN standards and expectations. This study employs a qualitative method based on a review of the literature and document analysis, guided by John P. Lovell’s Strategic Foreign Policy framework, to assess how national capability and external strategic dynamics affect state behavior. The results show that Timor Leste continuously applied Concordance and Accommodation Strategies, as evidenced by proactive diplomacy with ASEAN members, bureaucratic strengthening, and political reforms. Despite structural shortcomings, Timor Leste improved domestic stability through bilateral cooperation, labor mobility, and exports. Diplomatically, the country expanded its regional presence by opening embassies, joining ASEAN forums, and following the Roadmap for Full Membership. All these concerted steps at play helped reduce skepticism, particularly that of Singapore and Laos over the preparedness of Timor Leste. By 2025, ASEAN finally accepted Timor Leste as its eleventh member, after a decade-long journey of integration. This research contributes a comprehensive evaluation of the strategic foreign policy of Timor Leste during a critical temporal phase hitherto underexamined in the literature. Furthermore, it displays the importance of adaptive strategies for a small state seeking regional legitimacy within a complex geopolitical environment.